Processamento sísmico de um dado real marinho 2-D das Bacias de Tumbes-Progresso e Talara (PERU) - SENA, Caroline Thais Martins de (2019)
The reaction seismic provides the location of exploration targets through seismic data. The processing of seismic data is divided into three parts: pre-processing, processing and imaging. These data are recorded and processed through digital computational steps to produce images of the Earth's subsurface structures, then they are interpreted. This paper presents the main tools used in seismic data processing with each step described. One of many problems in seismic processing is the presence of multiple waves acting the quality of seismic sections providing, then, a difficult interpretation. In an attempt to attenuate multiple waves we used two techniques, Radon Filter and SRME (Surface-Related Multiple Elimination) and additional tools available in ProMAX R, however the result of the combination of these techniques has been unsatisfactory, because the sedimentary package of this basin users abrupt lateral variations of the velocity eld. thus we improved the velocity model to solve this problem . The object of this work is a 2-D seismic profile, RIB93-05 line. This problem was recorded by the company Peru Petro SA along two basins, Tumbes-Progresso e Talara, and we present a brief explanation of the geology and stratigraphy of these basins and show a migrated section of the cited profile.